Victors and Vanquished in the Euro-Mediterranean (Brill, 2025)
The volume presents a comparative perspective on victors and vanquished according to the categories of remembering victory and defeat, practices of celebrating victory and triumphs as well as the culture of dealing with the vanquished. Specifically, the representation of victory and defeat in Byzantine literature of the 10th–12th centuries is contrasted with commemorative practices in early Russia, and the reflection of military events in courtly music of the 15th century is examined. In addition, the practices of celebrating victories in England in the High and Late Middle Ages are explored, as is the treatment of the defeated and the subjugated in the Frankish Empire of the 9th century, in Norman southern Italy and in Byzantium.